Toward the application of metallothionein inducers as a method of prevention of air pollutant-dependent lung injury - Tanaka, Ken-ichiro (Frontiers in Public Health, 2025)
Although Sustainable Development Goal 3.9 states the global goal of reducing air pollution-related death and disease, innovative ways to reduce air pollution-related deaths and diseases have not yet been established. To address this issue, we have established animal models using urban air dust containing the major air pollutants, suspended particulate matter (PM10) and fine particulate matter (PM2.5), and are promoting research to discover protective factors in the respiratory tract where air pollutants first reach the human body. Therefore, in this Perspective manuscript, we provide an overview of our research on the preventive effects of the endogenous protein metallothionein on air pollutant-dependent lung injury and prospects for the clinical application of metallothionein inducers. We hope that this manuscript will help to solve health hazards caused by air pollution.